International secondary science grade 8 - " Fullrick, Ann" (Karachi; Oxford University Press, 2024)
The Oxford International Secondary Science book for Grade 8 provides a comprehensive overview of key scientific concepts, designed to engage and challenge students. It covers a range of topics, including biology, chemistry, and physics, with a focus on practical applications and real-world connections. The book includes interactive elements, hands-on activities, and assessments to support learning and ensure a thorough understanding of each subject. Its approach encourages critical thinking and problem-solving skills, preparing students for more advanced scientific study.
Keywords: Science